Picking Brains on a Global Scale: Practice Current and Practice Buzz. Issue 4 (August 2022) - Zea Vera, Alonso; Bartolini, Luca; Ganesh, Aravind
Abstract : When faced with challenging clinical situations, we often ask our colleagues: Can I pick your brain? As clinicians, we aim to provide evidence-based care, often presented as standardized protocols and guidelines. However, practice differences are frequently encountered when discussing challenging cases with peers. These may be more frequent among clinicians of different institutions and/or countries. The reasons for these variations are endless: lack of enough evidence, disparities in access to resources, local population characteristics, among others. Understanding these variations is important for a few key reasons. It can help us clarify the extent of equipoise vs consensus on different aspects of challenging or controversial topics in neurologic care or practice. It can reveal remarkable practice patterns that may have become entrenched despite an evidence vacuum. For researchers, innovators, and policymakers, it can reveal regional variations in practice patterns that will need to be accommodated or addressed when considering large-scale trials, quality improvement initiatives, or introducing new workflows or technologies. Yet few individuals or groups have access to a sufficiently widespread population of neurology practitioners—sampling within one's own personal or professional network can be misleading. So, what if you could pick the brains of neurology practitioners around the world?